Solid electrolyte and preparation method and application thereof

By using a high-entropy material with the chemical formula A(Li(3+x+2y)Zr(2-x-2y)MxNySi2PO12)B(Li3La(PO4)2), the problem of low conductivity of existing oxide solid-state lithium-ion electrolytes is solved, and a solid-state battery material with high lithium-ion conductivity and long life is achieved.

CN119812451AActive Publication Date: 2025-04-11广东伽瓦纳米科技有限公司

Patent Information

Application Number
CN202510170995.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-17
Publication Date
2025-04-11
Estimated Expiration
2045-02-17

AI Technical Summary

Technical Problem

The current oxide solid lithium-ion electrolyte has low conductivity and is difficult to synthesize under conditions below 700°C and improve the crystal development, which hinders its performance improvement and application prospects.

Method used

A solid electrolyte with the chemical formula A(Li(3+x+2y)Zr(2-x-2y)MxNySi2PO12)B(Li3La(PO4)2) is used to optimize the transmission path of lithium ions by adjusting the proportions of A and B and elements.

Benefits of technology

The solid electrolyte with high lithium ion conductivity is achieved, which improves the battery capacity and service life of the battery, and can be synthesized under conditions below 700°C, improving the performance and application prospects of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119812451A_ABST
    Figure CN119812451A_ABST
Patent Text Reader

Abstract

The invention provides a solid electrolyte, the chemical formula of the solid electrolyte is A (Li (3 + x + 2y) Zr (2-x-2y) MxNySi2PO12) B (Li3La (PO4) 2), A + B = 1, x is greater than or equal to 0 and less than or equal to 0.5, y is greater than or equal to 0.1 and less than or equal to 0.3, M is a trivalent metal ion, and N is a divalent metal ion. The solid electrolyte has the beneficial effects that the solid electrolyte disclosed by the invention has relatively high ionic conductivity; the battery prepared from the solid electrolyte disclosed by the invention has relatively high battery capacity and relatively long service life.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of lithium batteries, and in particular relates to a solid electrolyte and a preparation method and application thereof. Background Art

[0002] In the field of battery energy, lithium-ion secondary batteries have a dominant position in the fields of mobile electronic products and electric vehicles due to their high energy density, wide operating temperature range and long service life. Traditional lithium-ion batteries use organic solvent electrolyte liquids for lithium ion transmission. Organic solvent solutions are volatile and have a low ignition point, which can easily cause leakage, flatulence and other serious problems, and even lead to serious problems such as battery combustion and explosion, which poses a safety hazard. The use of solid electrolytes to prepare solid-state batteries instead of electrolytes can effectively avoid the safety hazards caused by the above organic solvents. At the same time, the negative electrode can use higher energy lithium metal to greatly increase the battery energy density.

[0003] Solid-state lithium-ion electrolyte Li (3+x+2y) Zr (2-x-2y) M x N y Si2PO 12 It has a very high room temperature lithium ion conductivity, and its conductivity can reach more than 10mS / cm. It is a very excellent lithium ion solid electrolyte material. This material is a high entropy material composed of multiple phases such as LSZP+LLZO+LLPO formed by multiple divalent (Mg, Zn), trivalent (La, Fe, Al), and tetravalent (Zr, Si) metal oxides. It has multidimensional lithium ion channels. This structure enables the material to have high room temperature lithium ion conductivity (>10mS / cm), but this material contains LZSP phase. The synthesis method is to carry out ion replacement under high temperature conditions of 180°C, that is, to replace the sodium ions in NZSP with lithium salts in a high-temperature organic solvent. Because this material has a metastable structure, its layered structure will be destroyed when the temperature exceeds 700°C. That is, the existing synthesis method cannot effectively solve the uniform distribution of Li, Mg, Zn, La, Fe, Al, Zr, Si, and PO4 ions in the solution, nor can it be synthesized at below 700°C and make the crystals develop perfectly without amorphous powder, which seriously hinders its performance improvement and application prospects. Summary of the invention

[0004] The present application provides a solid electrolyte and a preparation method and application thereof, aiming to solve the problem of low conductivity of existing oxide solid lithium ion electrolytes.

[0005] The first aspect of the present application provides a solid electrolyte, the chemical formula of which is A(Li (3+x+2y) Zr (2-x-2y) M x N y Si2PO 12)B(Li3La(PO4)2), wherein A+B=1, 0≤x≤0.5, 0.1≤y≤0.3, M is a trivalent metal ion, and N is a divalent metal ion. The solid electrolyte described in the present application is a complex locally disordered high-entropy material including layered, cubic, and fluorite structures formed by a variety of divalent, trivalent, and tetravalent oxides and phosphates. This structure facilitates the generation of overlapping site energy distributions for lithium ions, thereby reducing the energy difference of the permeation network of the connection points and accelerating the lithium ion transmission accordingly. The changes in the ion paths produced by the different elemental compositions in the high-entropy material open up permeation paths for the rapid movement of lithium ions in the low-mobility lattice, thereby forming ultra-high lithium ion conductivity.

[0006] According to some embodiments of the solid electrolyte described in the present application, M includes La 3+ , Fe 3+ and Al 3+ One or more of N including Mg 2+ and / or Zn 2+ .

[0007] The second aspect of the present application provides a composition for preparing the solid electrolyte described in the first aspect of the present application, comprising a lithium source, a zirconium source, a silicon source, a phosphorus source, an M source and a N source.

[0008] According to some embodiments of the composition described herein, the lithium source includes one or more of lithium nitrate, lithium carbonate and lithium chloride.

[0009] According to some embodiments of the composition described herein, the zirconium source includes one or more of zirconium oxychloride, zirconium nitrate, zirconium carbonate and zirconium ammonia carbonate.

[0010] According to some embodiments of the composition described herein, the silicon source includes one or more of sodium silicate nonahydrate, ethyl silicate and silica sol.

[0011] According to some embodiments of the composition described herein, the phosphorus source includes triethyl phosphate and / or butyl phosphate.

[0012] According to some embodiments of the composition described herein, the M source includes one or more of lanthanum carbonate, lanthanum nitrate, iron nitrate and aluminum nitrate.

[0013] According to some embodiments of the composition described herein, the N source includes magnesium acetate and / or zinc nitrate.

[0014] According to some embodiments of the composition described in the present application, the molar ratio of the lithium source to the zirconium source is: 3:(0.3-2), for example, 3:0.3, 3:0.5, 3:1.0, 3:1.2, 3:1.5, 3:1.7, 3:2, etc.

[0015] The molar ratio of the lithium source to the silicon source is: (3-8):2, for example, 3:2, 3.3:2, 3.5:2, 5:2, 7:2, 8:2, etc.

[0016] The molar ratio of the lithium source to the phosphorus source is: (1-3.5):1, for example, 1:1, 2:1, 3:1, 3.2:1, 3.3:1, 3.5:1, etc.

[0017] The molar ratio of the lithium source to the M source is: (3-3.6): (0.1-0.5).

[0018] The molar ratio of the lithium source to the N source is: (3-3.6): (0.1-0.3).

[0019] The third aspect of the present application provides a method for preparing the solid electrolyte described in the first aspect of the present application, which is prepared using the composition described in the second aspect of the present application.

[0020] According to some embodiments of the method for preparing the solid electrolyte described in the present application, the following steps are included:

[0021] (1) mixing a lithium source, a zirconium source, a silicon source, a M source, a N source and a solvent to obtain a mixed solution;

[0022] (2) mixing the mixed solution and a phosphorus source to react to obtain a gel;

[0023] (3) heating the gel to obtain a precursor material;

[0024] (4) calcining the precursor material to obtain the solid electrolyte.

[0025] According to some embodiments of the solid electrolyte preparation method described in the present application, in step (1), the solvent includes ethanol and / or acetic acid.

[0026] According to some embodiments of the solid electrolyte preparation method described in the present application, the mixing temperature is: 20-30°C, for example, 20°C, 25°C, 28°C, 30°C, etc., and the mixing time is 1-2h, for example, 1h, 1.2h, 1.5h, 1.8h, 2h, etc.

[0027] According to some embodiments of the solid electrolyte preparation method described in the present application, in step (2), the reaction temperature is 50-60°C, for example, 50°C, 52°C, 55°C, 58°C, 60°C, etc., and the reaction time is 3-5h, for example, 3h, 4h, 5h, etc.

[0028] According to some embodiments of the solid electrolyte preparation method described in the present application, in step (3), the heating is microwave heating.

[0029] According to some embodiments of the solid electrolyte preparation method described in the present application, the temperature of the microwave heating is 90-110°C, for example, 90°C, 95°C, 100°C, 105°C, 110°C, etc., and the time of the microwave heating is 1-2h, for example, 1h, 1.2h, 1.5h, 1.8h, etc.

[0030] According to some embodiments of the solid electrolyte preparation method described in the present application, in step (4), the calcination temperature is 450-700°C, for example, 450°C, 480°C, 500°C, 550°C, 580°C, 620°C, 650°C, 680°C, 700°C, etc., and the calcination time is 5-8h, for example, 5h, 6h, 7h, 8h, etc.

[0031] According to some embodiments of the method for preparing a solid electrolyte described in the present application, the method for preparing a solid electrolyte further comprises cleaning, grinding and drying the product obtained by calcination.

[0032] The fourth aspect of the present application provides an application of the solid electrolyte described in the first aspect of the present application or the solid electrolyte obtained by the preparation method described in the third aspect of the present application in lithium batteries.

[0033] The beneficial effects of the present application include: the solid electrolyte described in the present application has a high ionic conductivity. The battery prepared by the solid electrolyte described in the present application has a high battery capacity and service life. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] Figure 1 This is the XRD spectrum of the solid electrolyte prepared in Example 1 of the present application;

[0035] Figure 2 This is the XRD spectrum of the solid electrolyte prepared in Example 2 of the present application;

[0036] Figure 3 This is the XRD spectrum of the solid electrolyte prepared in Example 3 of the present application;

[0037] Figure 4 This is the XRD spectrum of the solid electrolyte prepared in Example 4 of the present application. DETAILED DESCRIPTION

[0038] Embodiments of the present invention are described in detail below, and examples of the embodiments are shown in the accompanying drawings. The embodiments described below with reference to the accompanying drawings are exemplary and intended to be used to explain the present invention, but should not be understood as limiting the present invention.

[0039] In the present invention, the terms "one embodiment", "some embodiments", "examples", "specific examples", or "some examples" etc. mean that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the described specific features, structures, materials or characteristics may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.

[0040] Example 1

[0041] A method for preparing a solid electrolyte comprises the following steps:

[0042] (1) 220.8 g of anhydrous lithium nitrate (3.2 mol), 481.09 g of zirconium nitrate (1.8 mol), 429.14 g of ethyl silicate (SiO2 content 28%), 64.98 g of lanthanum nitrate, 14.2 g of magnesium acetate and 2000 g of ethanol were mixed and reacted at a temperature of 20° C. for 1 hour to obtain a mixed solution; wherein the molar ratio of lithium nitrate, zirconium nitrate, ethyl silicate, lanthanum nitrate and magnesium acetate was 3.2:1.8:0.3:0.2:0.1;

[0043] (2) reacting the mixed solution obtained in step (1) with 182.16 g of triethyl phosphate at 50° C. under vacuum conditions for 3 h to obtain a gel;

[0044] (3) The gel obtained in step (2) is subjected to microwave heating at a temperature of 100° C. for a heating time of 1 h to obtain a powdered precursor, which is then calcined at a temperature of 700° C. for 8 h. The precursor is naturally cooled to room temperature, and the calcined product is washed with deionized water and anhydrous ethanol in turn, the washed calcined product is ground, and then the ground product is spray-dried to obtain a powdered precursor having a chemical formula of Li 3.2 Zr 1.8 La 0.2 Mg 0.1 Si2PO 12 of solid electrolytes.

[0045] Example 2

[0046] The only difference between Example 2 and Example 1 is that the amount of lanthanum nitrate added during the preparation of the solid electrolyte in Example 2 is different from that in Example 1.

[0047] The specific steps include:

[0048] (1) 220.8 g of anhydrous lithium nitrate (3.2 mol), 481.09 g of zirconium nitrate (1.8 mol), 429.14 g of ethyl silicate (SiO2 content 28%), 97.48 g of lanthanum nitrate, 14.2 g of magnesium acetate and 2000 g of ethanol were mixed and reacted at a temperature of 20° C. for 1 hour to obtain a mixed solution; wherein the molar ratio of lithium nitrate, zirconium nitrate, ethyl silicate, lanthanum nitrate and magnesium acetate was 3.2:1.8:0.3:0.3:0.1;

[0049] (2) reacting the mixed solution obtained in step (1) with 182.16 g of triethyl phosphate at 50° C. under vacuum conditions for 3 h to obtain a gel;

[0050] (3) The gel obtained in step (2) is subjected to microwave heating at a temperature of 100° C. for a heating time of 1 h to obtain a powdered precursor, which is then calcined at a temperature of 700° C. for 8 h. The precursor is naturally cooled to room temperature, and the calcined product is washed with deionized water and anhydrous ethanol in turn, the washed calcined product is ground, and then the ground product is spray-dried to obtain a powdered precursor having a chemical formula of Li 3.2 Zr 1.8 La 0.3 Mg 0.1 Si2PO 12 of solid electrolytes.

[0051] Example 3

[0052] The only difference between Example 3 and Example 1 is that the amount of lanthanum nitrate added during the preparation of the solid electrolyte in Example 3 is different from that in Example 1.

[0053] The specific steps include:

[0054] (1) 220.8 g of anhydrous lithium nitrate (3.2 mol), 481.09 g of zirconium nitrate (1.8 mol), 429.14 g of ethyl silicate (SiO2 content 28%), 129.97 g of lanthanum nitrate, 14.2 g of magnesium acetate and 2000 g of ethanol were mixed and reacted at a temperature of 20° C. for 1 hour to obtain a mixed solution; wherein the molar ratio of lithium nitrate, zirconium nitrate, ethyl silicate, lanthanum nitrate and magnesium acetate was 3.2:1.8:0.3:0.4:0.1;

[0055] (2) reacting the mixed solution obtained in step (1) with 182.16 g of triethyl phosphate at 50° C. under vacuum conditions for 3 h to obtain a gel;

[0056] (3) The gel obtained in step (2) is subjected to microwave heating at a temperature of 100° C. for a heating time of 1 h to obtain a powdered precursor, which is then calcined at a temperature of 700° C. for 8 h. The precursor is naturally cooled to room temperature, and the calcined product is washed with deionized water and anhydrous ethanol in turn, the washed calcined product is ground, and then the ground product is spray-dried to obtain a powdered precursor having a chemical formula of Li 3.2 Zr 1.8 La 0.4 Mg 0.1 Si2PO 12 of solid electrolytes.

[0057] Example 4

[0058] The only difference between Example 4 and Example 1 is that the amount of magnesium acetate added during the preparation of the solid electrolyte described in Example 4 is different from that in Example 1.

[0059] The specific steps include:

[0060] (1) 220.8 g of anhydrous lithium nitrate (3.2 mol), 481.09 g of zirconium nitrate (1.8 mol), 429.14 g of ethyl silicate (SiO2 content 28%), 64.98 g of lanthanum nitrate, 28.4 g of magnesium acetate and 2000 g of ethanol were mixed and reacted at a temperature of 20° C. for 1 hour to obtain a mixed solution; wherein the molar ratio of lithium nitrate, zirconium nitrate, ethyl silicate, lanthanum nitrate and magnesium acetate was 3.2:1.8:0.3:0.2:0.2;

[0061] (2) reacting the mixed solution obtained in step (1) with 182.16 g of triethyl phosphate at 50° C. under vacuum conditions for 3 h to obtain a gel;

[0062] (3) The gel obtained in step (2) is subjected to microwave heating at a temperature of 100° C. for a heating time of 1 h to obtain a powdered precursor, which is then calcined at a temperature of 700° C. for 8 h. The precursor is naturally cooled to room temperature, and the calcined product is washed with deionized water and anhydrous ethanol in turn, the washed calcined product is ground, and then the ground product is spray-dried to obtain a powdered precursor having a chemical formula of Li 3.2 Zr 1.8 La 0.2 Mg 0.2 Si2PO 12 of solid electrolytes.

[0063] Comparative Example 1

[0064] The difference between Comparative Example 1 and Example 1 is that the raw material lanthanum nitrate is not added in the solid electrolyte preparation process of Comparative Example 1, and the rest of the operations are the same as those of Example 1.

[0065] Comparative Example 2

[0066] The difference between Comparative Example 2 and Example 1 is that the raw material magnesium acetate is not added in the solid electrolyte preparation process of Comparative Example 2, and the rest of the operations are the same as those of Example 1.

[0067] Comparative Example 3

[0068] The difference between Comparative Example 3 and Example 1 is that the raw materials lanthanum nitrate and magnesium acetate are not added during the preparation of the solid electrolyte in Comparative Example 3, and the remaining operations are the same as those in Example 1.

[0069] Comparative Example 4

[0070] The solid electrolyte described in Comparative Example 4 is a LATP oxide electrolyte.

[0071] Comparative Example 5

[0072] The solid electrolyte described in Comparative Example 5 is an oxide solid electrolyte LLZO.

[0073] Performance study of the solid electrolytes described in Examples 1-4 and Comparative Examples 1-5 of the present application

[0074] The solid electrolytes described in Examples 1-4 and Comparative Examples 1-5 of the present application were weighed respectively, and hot pressed at 30 MPa and 700° C. Then, the samples were repeatedly sprayed with gold using an ion sputtering instrument, and the room temperature conductivity was tested using SP-300 at 0.1 Hz-7 MHz and ±1 V (10 pieces were tested in each group, and the average value was calculated). The test results are shown in Table 1.

[0075] Table 1

[0076]

[0077] It can be seen from Table 1 that the solid electrolyte described in this application can be used to prepare oxide solid electrolytes with very high ionic conductivity in large quantities and stably at a low cost through multi-element doping. At present, most oxide solid electrolytes have a high Young's modulus, and the poor interface matching with the positive electrode material in the solid-state battery seriously affects the performance. The solid electrolyte A (Li (3+x+2y) Zr (2-x-2y) M x N y Si2PO 12 )B(Li3La(PO4)2)Solid-state electrolytes with high ionic conductivity and low Young's modulus can be prepared by adjusting the ratio of A and B.

[0078] This application describes the above embodiments. It can be understood that the above embodiments are exemplary and cannot be understood as limitations of the present invention. Changes, modifications, substitutions and variations of the above embodiments made by ordinary technicians in this field are all within the protection scope of the present invention.

Claims

1. A solid electrolyte, characterized in that The chemical formula of the solid electrolyte is: A(Li (3+x+2y) Zr (2-x-2y) M x N y Si2PO 12 )B(Li3La(PO4)2), wherein A+B=1, 0≤x≤0.5, 0.1≤y≤0.3, M is a trivalent metal ion, and N is a divalent metal ion.

2. The solid electrolyte according to claim 1, characterized in that M includes La 3+ , Fe 3+ and Al 3+ One or more of N including Mg 2+ and / or Zn 2+ .

3. A composition for preparing the solid electrolyte according to any one of claims 1 to 2, characterized in that: Including lithium source, zirconium source, silicon source, phosphorus source, M source and N source; Preferably, the lithium source includes one or more of lithium nitrate, lithium carbonate and lithium chloride; Preferably, the zirconium source includes one or more of zirconium oxychloride, zirconium nitrate, zirconium carbonate and zirconium ammonia carbonate; Preferably, the silicon source includes one or more of sodium silicate nonahydrate, ethyl silicate and silica sol; Preferably, the phosphorus source includes triethyl phosphate and / or butyl phosphate; Preferably, the M source comprises one or more of lanthanum carbonate, lanthanum nitrate, iron nitrate and aluminum nitrate; Preferably, the N source comprises magnesium acetate and / or zinc nitrate.

4. The composition for preparing a solid electrolyte according to claim 3, characterized in that the molar ratio of the lithium source to the zirconium source is: 3: (0.3-2); The molar ratio of the lithium source to the silicon source is: (3-8): 2; The molar ratio of the lithium source to the phosphorus source is: (1-3.5): 1; The molar ratio of the lithium source to the M source is: (3-3.6): (0.1-0.5); The molar ratio of the lithium source to the N source is: (3-3.6): (0.1-0.3).

5. The method for preparing the solid electrolyte according to any one of claims 1 to 2, characterized in that: The composition is prepared by using any one of claims 3-4.

6. The method for preparing the solid electrolyte according to claim 5, characterized in that: The following steps are involved: (1) mixing a lithium source, a zirconium source, a silicon source, a M source, a N source and a solvent to obtain a mixed solution; (2) mixing the mixed solution and a phosphorus source to react to obtain a gel; (3) heating the gel to obtain a precursor material; (4) calcining the precursor material to obtain the solid electrolyte.

7. The method for preparing the solid electrolyte according to claim 6, characterized in that: In step (1), the solvent comprises ethanol and / or acetic acid; And / or, the mixing temperature is 20-30° C., and the mixing time is 1-2 h.

8. The method for preparing a solid electrolyte according to claim 6, characterized in that: In step (2), the reaction temperature is 50-60°C and the reaction time is 3-5h; And / or, in step (3), the heating is microwave heating; preferably, the temperature of the microwave heating is 90-110° C., and the time of the microwave heating is 1-2 h; And / or, in step (4), the calcination temperature is 450-700° C., and the calcination time is 5-8 hours.

9. The method for preparing a solid electrolyte according to claim 6, characterized in that: The method for preparing the solid electrolyte further comprises washing, grinding and drying the calcined product.

10. Use of the solid electrolyte according to any one of claims 1 to 2 or the solid electrolyte obtained by the preparation method according to any one of claims 5 to 9 in lithium batteries.

Citation Information

Patent Citations

  • Manganese-doped lithium-zirconium-silicon-phosphorus-oxygen solid electrolyte material as well as preparation method and application thereof

    CN116581369A

  • Halogen element doped and modified LZSP solid electrolyte material and preparation method and application thereof

    CN117393842A

  • In-situ reactive solid electrolyte membrane and preparation method thereof

    CN118380636A

  • High-entropy NASICON type solid electrolyte with high conductivity

    CN119447434A

  • Solid electrolyte and a lithium-ion conductive glass-ceramics

    EP3993122A1

Cited By

  • Method of preparing a composite solid-state electrolyte composition based on in-situ polymerization of a precursor powder, composite solid-state electrolyte membrane and solid-state battery

    CN122677517A